Postępy w nauce studentów pracujących według ich cech demograficznych - Olejniczak, Alicja (Wydział Prawa i Administracji UAM, 1972)
The purpose of the paper is to determine the influence of selected demographic and social factors upon the progress in studies achieved by students who earn their living. The strength and direction of the influence were traced by help of covrelation and regression analysis. The sources that have been used are personal documents of applicants which are kept in the College office and records of marks obtained in examinations. One of the personal documents is „The Applicant's Card" that supplies information concerning the year of birth, number of children in the family that the applicant comes from, civil status, number of children to maintain, the year of the children's birth, the year of leaving secondary school and the type of secondary school. The authoress has come to the following conclusions: The age of the applicants or students is most frequently negatively correlated with their progress in studies. A hypothesis about a correlation between the number of children in the family the applicant comes from and his progress in studies cannot be upheld. In case of applicants and students who are married women there is a negative relation between the number of children and the marks obtained in examinations. On the other hand in case of married men the relation is occasionally positive. Between the average age of the children of the applicants and students and the marks obtained in examinations there is generally a positive relations. Only in some cases the above mentioned relations are expressed by significant correlation coefficients.
Progress Studies Achieved by Students Earning Their Living, by Demographic Characteristics